White Light Emission: A Full Vacuum Approach for the Fabrication of Hybrid White‐Light‐Emitting Thin Films and Wide‐Range In Situ Tunable Luminescent Microcavities (Advanced Optical Materials 7/2016). Issue 7 (20th July 2016) - Oulad‐Zian, Youssef; Sanchez‐Valencia, Juan Ramon; Oliva, Manuel; Parra‐Barranco, Julian; Alcaire, Maria; Aparicio, Francisco J.; Mora‐Boza, Ana; Espinos, Juan Pedro; Yubero, Francisco; Gonzalez‐Elipe, Agustin R.; Barranco, Angel; Borras, Ana
Abstract : A wide‐range in situ tunable 1D Bragg microcavity including a hybrid layer as white light emitter defect is shown by J. R. Sanchez‐Valencia, A. Borras, and co‐workers on page 1124. White emission is obtained by Förster resonance energy transfer between blue (1, 3, 5‐triphenyl‐2‐pyrazoline) and orange (rubrene) dyes homogeneously infiltrated within the host nanocolumnar SiO2 film, which is formed by glancing angle deposition. Sequential physical vapor deposition at low temperatures provides the organic dyes localization within the porous nanostructure of the defect layer.